Streambank, soil, and vegetation responses to grazing in a montane riparian ecosystem - Jolley, Leonard Warren, author; Trlica, M. J., advisor; Frasier, David, committee member; Steingraeber, David A., committee member; Wohl, Ellen, committee member; Smith, Jim, committee member (Colorado State University. Libraries, 2006)
Riparian areas in the western United States represent 2% or less of the available public and private lands historically used for grazing. Riparian zones are frequently used by grazing livestock and by many wildlife species. Riparian vegetation also influences streambank stability, water quality, and sediment filtration. Riparian communities are often the most productive areas, with deeper and more fertile soils compared with the surrounding uplands. Understanding the impacts of present and past grazing use on riparian zones, and how this use has influenced soil and plant characteristics, may help managers better understand how grazing use may influence streambank stability, roots, and soil characteristics. One part of this research effort was conducted with a mechanical hoof simulator to measure the direct chiseling impact of hoof prints on streambanks. The objective of this study was to relate the imprints from a hoof simulator on a streambank with variables such as soil texture, soil organic matter, plant community composition, root biomass, and root length density, and as influenced by grazing history. A second study of soil matrix shear strength was conducted to further characterize resilience of streambank soils based on grazing use. The objective of this study was to determine the shear strength of soil cores and evaluate soil and vegetative characteristics that could be used to predict shear strength. Soil bulk density for the 0-10 cm depth increased as long-term grazing history increased from exclosures, to 8 years of grazing, to long-term (+ 40 years) grazing. Whereas, soil shear strength values also appeared to follow this trend, (increasing to more than twice the strength in long-term grazed areas compared to exclosures), the differences were not significant. Organic matter declined over these same paddocks. Hoof impacts were found to be significantly greater when the soil surface was wet. Length of fine roots was significantly greater in exclosures. Carex dominated plant communities appeared to have greater soil shear strength than grass dominated communities. A third study was to relate riparian species root strength to root diameter to help explain soil-root matrix strength. Segments of riparian root samples were tested for tensile strength. Root diameter at the point of rupture was found to be highly correlated with root strength. Greater whole root strengths were found for species of sedges, rushes, and willows than for grasses and forbs. The observed pattern of root strength was greater for large roots of willows and least for grasses, with grass-like plants in the mid-range. The opposite was true for tensile strength values (force at failure/root cross-sectional area.) These and similar findings have management implications for land managers and public agencies for both domestic and wild grazing animals. This research supports the recommendation that, all other things being equal, grazing to achieve less soil surface disturbance should occupy time periods when the soil is dryer. This research also supports the long-term relationship between grazing, soil bulk density, soil organic matter, and rooting pattern. Results of soil shear strength within the three plant communities showed that the sedge/grass community would have the stronger soil strength when examined at the community level. This is partially explained by sedges root extension, root biomass, and root length density, all of which were greater in the sedge/grass community compared with the other two communities. The grass/rush community appeared to have the weakest soil stability (measured as shear strength, 50% less compared to the sedge/grass group). The grass/forb/shrub community had intermediate soil stability. These results indicated that individual root strength alone did not provide adequate explanation for soil stability (measured as soil shear strength) when compared at the plant community level. However, root abundance characteristics such as total root length, root biomass, and root length density may provide better predictive capabilities of soil stability when measured as soil shear strength within a plant community.
Keywords: range management